2012
DOI: 10.1007/s00280-012-2029-1
|View full text |Cite
|
Sign up to set email alerts
|

Early initiation of adjuvant chemotherapy improves survival of patients with pancreatic carcinoma after surgical resection

Abstract: Adjuvant chemotherapy for patients with resected pancreatic carcinoma should be initiated as soon as possible after surgical resection. Prevention of postoperative complication is needed to enable early initiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 35 publications
5
54
0
1
Order By: Relevance
“…1320 including PC. 3 Postoperative complications have been associated with worse long-term outcomes in esophageal cancer, 24,25 colorectal cancer, 2628 and PC. 4,22,29 However, the relationship between postoperative complications following PD for PC and receipt of adjuvant therapy is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1320 including PC. 3 Postoperative complications have been associated with worse long-term outcomes in esophageal cancer, 24,25 colorectal cancer, 2628 and PC. 4,22,29 However, the relationship between postoperative complications following PD for PC and receipt of adjuvant therapy is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the impact of postoperative complications on long-term survival in PC, 3,4,22,29 but only two have focused on TTA. 3,29 Murakami et al 3 reported median TTA for 104 patients was only 20 days and only postoperative complications related to longer TTA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the ESPAC-4 trial reported 5-year survival rates of 15% to 30% in patients with margin negative resection (R0) and adjuvant chemotherapy with either gemcitabine alone or gemcitabine in combination with capecitabine [4]. Local recurrence of the tumor occurs in up to 86% of surgical cases despite adjuvant chemotherapy [3], [4], [5], [7], [8], [9], [10]. More efficient adjuvant therapy regimens are being actively sought.…”
Section: Introductionmentioning
confidence: 99%
“…Ретроспективно проанализированная база данных SEER показала, что эф-фективность химиотерапии при III стадии рака поджелу-дочной железы в случае ее начала в сроки, превышающие 12 недель после операции, имеет тенденцию к снижению [12]. Нецелесообразность длительной отсрочки начала адъювантной химиотерапии подчеркивается и результа-тами других анализов [13,14].…”
unclassified